Medication adherence and therapeutical outcome in hypertension patients at the Mlati II health center - Lestari, Mardiana Puji; Sari, Dewi Puspita (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Hypertension is a chronic disease that needs to be treated properly and continuously. One of the critical successes of therapy is medication adherence by patients.Objective: Determine the correlation between medication adherence and therapeutic outcome in hypertension patients at the Mlati II health center.Methods: This is a non-experimental study with a cross sectional design analysis, by purposive sampling technique. Adherence was obtained in the form of adherence levels measured using the MMAS-8 questionnaire, therapeutic outcomes assessed by measuring a patient's blood pressure. Then the data were analyzed using the Chi-square test to determine the relationship between the level of adherence and therapeutic outcomes.Results: From 76 hypertension patients, the majority aged 46-55 years (44.7%), female gender (69.7%), senior high school (39.5%), employment status did not work (55.3%), long suffering from hypertension <5 years (76.3%), received single therapy (61.8%) with the type of antihypertension drug amlodipine (59.2%), low adherence category rate (39.5%), outcome of therapy with uncontrolled blood pressure (60,5%), and significancy level p = 0,997>0,05Conclusion: There is no relationship between the level of adherence to the use of antihypertension drugs and the outcome therapy of controlled blood pressure at the Mlati Il health center